Effects of "Owned-by" Versus "Made-in" for Willingness to Buy Australian Brands - Cheah, Isaac; Phau, Ian (Australian and New Zealand Marketing Academy, 2012)
This paper aims to examine the effects of economic nationalistic tendencies on consumer’s willingness to buy bi-national brands (i.e. product brands that involve affiliations of two or more countries - such as branded and made in Australia but owned by the French or the United States). By examining the Australian consumer’s economic nationalism towards bi-national brands, the study’s findings revealed a high level of economic nationalism present that resulted in the Australian consumers’ unwillingness to buy bi-national brands. More importantly, results showed that the Australian consumer’s are not any more receptive to bi-national brands as such domestic affiliations have not diluted the economic nationalistic sentiment.